2008
DOI: 10.1590/s1517-83822008000300001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pasture soil productivity in the semi-arid zone of Brazil by microbial analyses

Abstract: The productivity of a pasture soil (caatinga) located in the region of São João do Cariri, PB, Brazil was evaluated based an the following microbiological parameters: biomass (measured by fumigation-incubation method), activity (estimated from basal respiration and cellulose decomposition rate), qCO2, and Cmic : Corg ratio. This analysis demonstrated that livestock management in the ‘caatinga’ is probably causing environment damage by affecting the soil properties, reducing the microbial biomass and soil respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Anderson & Domsch (1993) proposed the utilization of the qCO 2 to estimate the efficiency of substrate use by soil organisms. The qCO 2 was lowest in forest and pasture soils, in agreement with Luna et al (2008), who reported that the qCO 2 decreases in more stable agroecosystems. These values were different compared with cultivated and capoeira soils; the qCO 2 increased 350 % in the cultivated area compared with the forest area.…”
Section: Br Mbc and Qcosupporting
confidence: 91%
“…Anderson & Domsch (1993) proposed the utilization of the qCO 2 to estimate the efficiency of substrate use by soil organisms. The qCO 2 was lowest in forest and pasture soils, in agreement with Luna et al (2008), who reported that the qCO 2 decreases in more stable agroecosystems. These values were different compared with cultivated and capoeira soils; the qCO 2 increased 350 % in the cultivated area compared with the forest area.…”
Section: Br Mbc and Qcosupporting
confidence: 91%
“…During the dry season, the highest q CO 2 rates were recorded with increasing proportions of lead-contaminated soil (Figure 3), which indicates that the ecosystem was under stress. These results show that microbial populations invest most of their energy for maintenance, a typical condition of disturbed environments (21). …”
Section: Resultsmentioning
confidence: 75%
“…Africa: Venter, Scholes & Eckhardt 2003; AGIS, http://www.agis.agric.za, 3. South America: Furley 1999; Moreira 2000Leal, Wirth & Tabarelli 2007; de Luna, Coutinho & Grisi 2008.…”
Section: Methodsmentioning
confidence: 99%